HUBUNGAN PENGETAHUAN MENGENAI GIZI, PENDAPATAN KELUARGA DAN INFESTASI SOIL TRANSMITTED HELMINTHS DENGAN KURANG ENERGI KRONIK (KEK) PADA IBU HAMIL DI DAERAH PESISIR SUNGAI SIAK PEKANBARU - Lidia Wati; Yanti Ernalia; Lilly Haslinda (Jurnal Online Mahasiswa (JOM) Bidang Kedokteran, 2014)
Chronic Energy Deficiency (CED) is a condition with a poor nutrition status of person caused by lack consumpting foods which contain macro nutrients for a long time or chronic. Chronic Energy Deficiency (CED) in pregnant women can caused by imbalance of nutrient intake and infectious disease. The purpose of this study is to discover the relationship between knowledge of nutrition, family income and soil transmitted helminths infestation with Chronic Energy Deficiency (CED) to pregnant women. This study includes the type of analytic study using cross sectional approach. Total samples are 30 people, sampling technique is total sampling. The result showed that of the 30 respondents known as 8 people (26,7%) experiencing chronic energy malnutrition in pregnancy. Analyzing data used Fisher test showed that there is a significant relationship between knowledge of nutrition with chronic energy deficiency to pregnant women and there is no significant relationship between family income and soil transmitted helminths infestation with chronic energy deficiency to pregnant women.Key words: kurang energi kronik, status gizi, pengetahuan, pendapatan keluarga, infestasi soil transmitted helminths